The Effectiveness of Education in Improving Knowledge and Preventive Behaviors Regarding Toxoplasmosis among Non-Health Female Students at the University of Bengkulu - Dessy Triana; Octavia Puspitha Sari; Meisa Nazthasia (CV. Wadah Publikasi Cendekia, 2026)
Toxoplasma gondii is a parasite responsible for toxoplasmosis, which demonstrates a high prevalence among women of reproductive age. Limited awareness places female students outside health sciences at an elevated risk of infection. While educational interventions have the potential to enhance both knowledge and preventive behaviors, the relationship between these factors in this population remains insufficiently studied. This research sought to determine the association between knowledge levels and toxoplasmosis prevention behaviors following an educational intervention. Utilizing a quasi-experimental one-group pre–posttest design, 153 participants were involved. Data collection was conducted via questionnaires, with analysis performed using the Wilcoxon test to compare pre- and post-intervention results and the Spearman Rank test to assess the correlation between knowledge and preventive behaviors after the intervention. Findings revealed a significant improvement in knowledge scores, rising from 10.63±3.665 to 16.89±2.456 (p < 0.001), as well as in preventive behavior scores, which increased from 36.39±6.560 to 48.80±4.756 (p < 0.001). A significant, albeit very weak, positive correlation between knowledge and preventive behaviors was observed (r = 0.256; p = 0.002). The educational intervention effectively enhanced both knowledge and toxoplasmosis prevention behaviors among non-health sciences female students at the University of Bengkulu, with a notable positive association identified between these variables post-intervention.